Copy number variations mediate major pathological response to induction chemo-immunotherapy in unresectable stage IIIA-IIIB lung cancer. (April 2023) - Zeng, Liang; Zhou, Yuling; Zhang, Xiangyu; Xu, Qinqin; Zhou, Chunhua; Zeng, Fanxu; Jiang, Wenjuan; Wang, Zhan; Deng, Li; Yang, Haiyan; Liu, Li; Xiong, Yi; et al.
Highlights: Induction chemo-immunotherapy promote surgery conversion rate (74.4%) in unresectable stage IIIA-IIIB lung cancer. The major pathological response (MPR) rate for induction chemo-immunotherapy was 65.6%. 73% of patients with N2 disease demonstrated down-staging to N0 after chemo-immunotherapy. Copy number variation (CNV) ploidy serve as a predictive biomarker for patients achieved MPR. Abstract: Introduction: Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. Despite this, evidence supporting optimal management of certain stages remains a topic of debate. In this retrospective study we examine the efficacy and safety, as well as exploring the biomarkers of neoadjuvant induction immuno-chemotherapy, in Chinese patients with unresectable stage III NSCLC. Methods: Patients with unresectable stage III NSCLC who were identified as driver mutation-negative and who received neoadjuvant chemo-immunotherapy were enrolled from three Chinese hospitals between Jan. 17, 2019, and Jan.17, 2022. Perioperative outcomes and survival data were collected. Retrospective biomarker exploration was performed in available baseline tumor samples and surgical specimens. Results: 94 patients were enrolled and received chemo-immunotherapy as neoadjuvant treatment. 80 patients had squamous cell carcinoma, and 26 had stage IIIB disease. Surgery conversion rate was 74.4%, R0 resection rate was 98.4%. Of 64 patients who underwent surgery, major pathological response (MPR) rate was 65.6% and pathologic complete response (pCR) rate was 42.2%. 73% of patients with N2 disease demonstrated down-staging to N0. Treatment-related adverse events (TRAEs) occurred in 43 patients (45.7%) with anemia was the most common. The Grade ≥ 3 TRAEs rate was 3.2% (3/94). A significant association between copy number variation (CNV) ploidy was also found. Conclusion: The combination treatment of immuno-chemotherapy for unresectable stage III NSCLC is not only effective but also has a favourable safety profile. For the first time we provide evidence that CNV status may be a predictive biomarker of MPR.